Food waste from Parkia biglobosa seed processing as a potential biomass resource for valorization - Oludipe, Emmanuel Olorunleke; Ajayi, Ayodele Oluwaseun; Owolabi, Akinyomade Oladipo; Olojede, Ayoyinka Olufunke; Afolabi, Yemisi Tokunbo; Nwonuma, Charles Obiora; Adewumi, Blessing Grace; Dada, Ebenezer Olasunkanmi; Owa, Stephen Oluwagbemiga (Frontiers in Sustainable Food Systems, 2024)
Introduction The valorization of agricultural waste from indigenous sub-Saharan African food processes remains underexplored. By-products from the processing of Parkia biglobosa seeds into condiments are often regarded as pollutants. This research assessed their potential for development in various industrial applications. Materials and methods This study employed a standardized protocol adopted in the processing of P. biglobosa seed into condiments, enabling the quantification of food and by-products generated as a percentage. A comparative analysis of the proximate and mineral constituents of the dried food condiment and seed coat (testa) was conducted. Furthermore, the phytochemical constituent of effluents from the two stages of processing was characterized using qualitative and quantitative methods, including Fourier-transform infrared spectroscopy (FTIR) and gas chromatography–mass spectrometry (GC–MS). Results and discussion The results showed that 66.27% of each 100 g processed P. biglobosa seed used could be considered waste, with 23.19% in seed coat and 29.47% in effluent(s). The seed coat has moisture absorption potential and is fibrous in nature, as confirmed by proximate fiber analysis—15.03 ± 0.13% compared to 9.07 ± 0.10% in the dried condiment. Both the condiments and seed coat contained considerable amounts of sustenance minerals. Effluents from the boiling process exhibited a characteristic starchy effect on textiles. The concentrated effluent from the first stage of boiling had a chocolate-like aroma, sticky texture, and dark-brown color compared to the effluent from the second boiling stage. The FTIR analysis indicated the presence of alcohols, alkenes, aromatic rings, carboxylic acids, and amines in the effluent samples. GCMS characterization reported the presence of specific fatty acids with known health benefits. When premised on the waste-to-wealth initiative, the quantified and characterized by-products of P. biglobosa seed processing, as reported in this study, have potential applications across various industrial processes, including food, cosmetics, pharmaceutical, and agriculture, among others.